Structure and function of a G-actin sequestering protein with a vital role in malaria oocyst development inside the mosquito vector - Hliscs, Marion; Sattler, Julia M.; Tempel, Wolfram; Artz, Jennifer D.; Dong, Aiping; Hui, Raymond; Matuschewski, Kai; Schüler, Herwig (The journal of biological chemistry, 2010)
Cyclase-associated proteins (CAPs) are evolutionary conserved G-actin-binding proteins that regulate microfilament turnover. CAPs have a modular structure consisting of an N-terminal adenylate cyclase binding domain, a central proline-rich segment, and a C-terminal actin binding domain. Protozoan parasites of the phylum Apicomplexa, such as Cryptosporidium and the malaria parasite Plasmodium, express small CAP orthologs with homology to the C-terminal actin binding domain (C-CAP). Here, we demonstrate by reverse genetics that C-CAP is dispensable for the pathogenic Plasmodium blood stages. However, c-cap(-) parasites display a complete defect in oocyst development in the insect vector. By trans-species complementation we show that the Cryptosporidium parvum ortholog complements the Plasmodium gene functions. Purified recombinant C. parvum C-CAP protein binds actin monomers and prevents actin polymerization. The crystal structure of C. parvum C-CAP shows two monomers with a right-handed β-helical fold intercalated at their C termini to form the putative physiological dimer. Our results reveal a specific vital role for an apicomplexan G-actin-binding protein during sporogony, the parasite replication phase that precedes formation of malaria transmission stages. This study also exemplifies how Plasmodium reverse genetics combined with biochemical and structural analyses of orthologous proteins can offer a fast track toward systematic gene characterization in apicomplexan parasites.